Upaya Meningkatkan Vocabulary Mastery dalam Pembelajaran Bahasa Inggris Melalui Metode Running Dictation Game - Dzulhijjah Yetti; Rahmad Akbar; Merlia Rahmayani; Andri Nofiar. Am; Antoni Pribadi (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
The objective of this study is to assess the improvement of English vocabulary mastery through the implementation of the running dictation game method among fifth-grade students at SDN 005 Langgini. This research adopts a Classroom Action Research (CAR) approach, conducted in two cycles with stages of planning, implementation, observation, and reflection. Data collection methods included observation, documentation, and question-and-answer sessions. The participants of the study were 31 fifth-grade students at SDN 005 Langgini. The data analysis techniques employed were descriptive qualitative and descriptive quantitative. The findings of the study reveal that the use of the running dictation game method significantly improved English vocabulary mastery among the fifth-grade students in class V C at SDN 005 Langgini. This improvement is evident in the increase in average student scores and the overall enhancement of vocabulary mastery. In the pre-cycle, the classical completeness rate was 20.42%, classified as Not Developing. The completeness rate improved to 52.63% in Cycle I, meeting the criterion of Developing as Expected. As the results from Cycle I did not meet the established success criteria, the study proceeded to Cycle II. In Cycle II, student completeness increased to 81.71%, meeting the criterion of Developing Very Well. In both written and oral tests, students demonstrated strong proficiency in mastering English vocabulary, including their ability to write, pronounce, and translate vocabulary accurately.